1998
DOI: 10.2337/diacare.21.11.1797
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of dobutamine-atropine stress echocardiography for the diagnosis of coronary artery disease in diabetic patients unable to perform an exercise stress test.

Abstract: Dobutamine stress echocardiography is a feasible method for the diagnosis of coronary artery disease in patients with limited exercise capacity with a comparable safety, feasibility, and accuracy in diabetic and nondiabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0
4

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 0 publications
1
39
0
4
Order By: Relevance
“…Although exercise ECG is the most common stress modality used for the noninvasive evaluation of CAD, exercise tolerance in diabetic patients may be impaired, particularly because of the higher prevalence of peripheral vascular disease. In the study by Elhendy et al (14), 13% of 1,446 consecutive patients with limited exercise capacity referred for evaluation of myocardial ischemia had an established diagnosis of diabetes. This emphasizes the central role of imaging techniques coupled with pharmacological stress for the diagnostic and prognostic assessment of CAD in these patients.…”
Section: Incremental Prognostic Value Of Sementioning
confidence: 99%
See 1 more Smart Citation
“…Although exercise ECG is the most common stress modality used for the noninvasive evaluation of CAD, exercise tolerance in diabetic patients may be impaired, particularly because of the higher prevalence of peripheral vascular disease. In the study by Elhendy et al (14), 13% of 1,446 consecutive patients with limited exercise capacity referred for evaluation of myocardial ischemia had an established diagnosis of diabetes. This emphasizes the central role of imaging techniques coupled with pharmacological stress for the diagnostic and prognostic assessment of CAD in these patients.…”
Section: Incremental Prognostic Value Of Sementioning
confidence: 99%
“…Therefore, assessing risk for cardiac events in these patients is a relevant clinical issue. Scintigraphic imaging techniques have greater prognostic value than exercise electrocardiography (ECG) in diabetic patients (13), whereas prognostic studies with stress echocardiography (SE) are still lacking, despite the proven safety, feasibility, and diagnostic effectiveness of this technique (14,15).…”
mentioning
confidence: 99%
“…However, exercise capacity is frequently impaired in diabetic patients, particularly because of the higher prevalence of peripheral neuropathy and vascular disease in this population (11)(12)(13)(14). Dobutamine stress echocardiography (DSE) has been reported as a safe and feasible method for evaluation of CAD in diabetic patients with limited exercise capacity (15,16). However, data regarding the incremental value of the technique in the risk stratification of diabetic patients are scarce (2).…”
mentioning
confidence: 99%
“…Although the study was limited by the small size of the cohort it demonstrated similar diagnostic accuracy for dobutamine stress echocardiography in a diabetic population as in the general population. In another study on 55 diabetics who underwent dobutamine stress echocardiography and www.intechopen.com angiography the sensitivity and specificity of stress echocardiography were 81% and 85% (Elhendy et al, 1998). The efficacy of dobutamine stress echocardiography was compared to exercise ECG testing and SPECT nuclear perfusion imaging in 56 asymptomatic diabetic patients with three additional cardiovascular risk factors but normal resting ECG.…”
Section: Stress Echocardiographymentioning
confidence: 99%